Synthesis and anion binding properties of phthalimide-containing corona[6]arenes - Gu, Meng-Di; Lu, Yao; Wang, Mei-Xiang (Beilstein Journal of Organic Chemistry, 2019)
Functionalized O6-corona[3]arene[3]tetrazines were synthesized efficiently and conveniently by means of a macrocyclic condensation reaction between N-functionalized 3,6-dihydroxyphthalimides and 3,6-dichlorotetrazine under mild conditions in a one-pot reaction manner. The novel macrocycles exist as a mixture of rapidly interconvertible conformers in solution while in the solid state they adopt the conformation in which three phthalimide units are cis,trans-orientated. Acting as electron-deficient macrocyclic hosts, the synthesized O6-corona[3]arene[3]tetrazines self-regulated conformational structures to complex anions in the gas phase and in the solid state owing to the anion–π noncovalent interactions between anions and the tetrazine rings.
Keywords: anion–π interactions; coronarenes; host–guest complexation; N-functionalized phthalimides; O6-corona[3]arene[3]tetrazines

Comprehensive Supramolecular Chemistry II - Atwood, J.; Gokel, G. W.; Barbour, L. (Elsevier, 2017)

Comprehensive Supramolecular Chemistry - Lehn, J.-M.; Atwood, J. L.; Davies, J. E. D.; MacNicol, D. D.; Vögtle, F. (Pergamon, 1996)

(untitled) - Wang, Q.-Q.; Luo, N.; Wang, X.-D.; Ao, Y.-F.; Chen, Y.-F.; Liu, J.-M.; Su, C.-Y.; Wang, D.-X.; Wang, M.-X. (J. Am. Chem. Soc., 2017)

(untitled) - Jiang, B.; Wang, W.; Zhang, Y.; Lu, Y.; Zhang, C.-W.; Yin, G.-Q.; Zhao, X.-L.; Xu, L.; Tan, H.; Li, X.; Jin, G.-X.; Yang, H.-B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Liu, Z.; Nalluri, S. K. M.; Stoddart, J. F. (Chem. Soc. Rev., 2017)

(untitled) - Ogoshi, T.; Yamagishi, T.-a.; Nakamoto, Y. (Chem. Rev., 2016)

(untitled) - Shetty, D.; Khedkar, J. K.; Park, K. M.; Kim, K. (Chem. Soc. Rev., 2015)

(untitled) - Jie, K.; Zhou, Y.; Yao, Y.; Huang, F. (Chem. Soc. Rev., 2015)

(untitled) - Han, Y.; Meng, Z.; Ma, Y.-X.; Chen, C.-F. (Acc. Chem. Res., 2014)

(untitled) - Wu, G.-Y.; Chen, L.-J.; Xu, L.; Zhao, X.-L.; Yang, H.-B. (Coord. Chem. Rev., 2018)

(untitled) - Sauvage, J.-P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Stoddart, J. F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Neel, A. J.; Hilton, M. J.; Sigman, M. S.; Toste, F. D. (Nature, 2017)

(untitled) - Galan, A.; Ballester, P. (Chem. Soc. Rev., 2016)

(untitled) - Zhang, H.; Yao, B.; Zhao, L.; Wang, D.-X.; Xu, B.-Q.; Wang, M.-X. (J. Am. Chem. Soc., 2014)

(untitled) - Zhang, Q.; Liu, Y.; Wang, T.; Zhang, X.; Long, C.; Wu, Y.-D.; Wang, M.-X. (J. Am. Chem. Soc., 2018)

(untitled) - Wang, M.-X. (Chem. Commun., 2008)

(untitled) - Wang, M.-X. (Acc. Chem. Res., 2012)

(untitled) - Maes, W.; Dehaen, W. (Chem. Soc. Rev., 2008)

(untitled) - Tsue, H.; Ishibashi, K.; Tamura, R. (Top. Heterocycl. Chem., 2008)

Calixarenes and Beyond - Neri, P.; Sessler, J. L.; Wang, M.-X. (Springer, 2016)
Chapters 14–16 and 18.

(untitled) - Wang, M.-X. (Sci. China: Chem., 2018)

(untitled) - Guo, Q.-H.; Fu, Z.-D.; Zhao, L.; Wang, M.-X. (Angew. Chem., Int. Ed., 2014)

(untitled) - Guo, Q.-H.; Zhao, L.; Wang, M.-X. (Angew. Chem., Int. Ed., 2015)

(untitled) - Fu, Z.-D.; Guo, Q.-H.; Zhao, L.; Wang, D.-X.; Wang, M.-X. (Org. Lett., 2016)

(untitled) - Wu, Z.-C.; Guo, G.-H.; Wang, M.-X. (Angew. Chem., Int. Ed., 2017)

(untitled) - Liu, H.-B.; Zhang, Q.; Wang, M.-X. (Angew. Chem., Int. Ed., 2018)

(untitled) - Guo, Q.-H.; Zhao, L.; Wang, M.-X. (Chem. – Eur. J., 2016)

(untitled) - Lu, Y.; Fu, Z.-D.; Guo, Q.-H.; Wang, M.-X. (Org. Lett., 2017)

(untitled) - Ren, W.-S.; Zhao, L.; Wang, M.-X. (Org. Lett., 2016)

(untitled) - Lu, Y.; Liang, D.-D.; Fu, Z.-D.; Guo, Q.-H.; Wang, M.-X. (Chin. J. Chem., 2018)

(untitled) - Gamez, P. (Inorg. Chem. Front., 2014)

(untitled) - Bauzá, A.; Mooibroek, T. J.; Frontera, A. (ChemPhysChem, 2015)

(untitled) - Zhao, Y.; Cotelle, Y.; Liu, L.; López-Andarias, J.; Bornhof, A.-B.; Akamatsu, M.; Sakai, N.; Matile, S. (Acc. Chem. Res., 2018)

(untitled) - Tuo, D.-H.; Liu, W.; Wang, X.-Y.; Wang, X.-D.; Ao, Y.-F.; Wang, Q.-Q.; Li, Z.-Y.; Wang, D.-X. (J. Am. Chem. Soc., 2019)

(untitled) - Luo, J.; Ao, Y.-F.; Wang, Q.-Q.; Wang, D.-X. (Angew. Chem., Int. Ed., 2018)

(untitled) - He, Q.; Ao, Y.-F.; Huang, Z.-T.; Wang, D.-X. (Angew. Chem., Int. Ed., 2015)

(untitled) - Wang, D.-X.; Zheng, Q.-Y.; Wang, Q.-Q.; Wang, M.-X. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wang, D.-X.; Wang, M.-X. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, D.-X.; Wang, Q.-Q.; Han, Y.; Wang, Y.; Huang, Z.-T.; Wang, M.-X. (Chem. – Eur. J., 2010)

(untitled) - Chifotides, H. T.; Schottel, B. L.; Dunbar, K. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Rosokha, Y. S.; Lindeman, S. V.; Rosokha, S. V.; Kochi, J. K. (Angew. Chem., Int. Ed., 2004)

(untitled) - Adriaenssens, L.; Gil-Ramírez, G.; Frontera, A.; Quiñonero, D.; Escudero-Adán, E. C.; Ballester, P. (J. Am. Chem. Soc., 2014)

(untitled) - Zhang, J.; Zhou, B.; Sun, Z.-R.; Wang, X.-B. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Anstöter, C. S.; Rogers, J. P.; Verlet, J. R. R. (J. Am. Chem. Soc., 2019)

(untitled) - Xi, J.; Xu, X. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Zheng, X.; Shuai, Z.; Wang, D. (J. Phys. Chem. A, 2013)

(untitled) - Clavier, G.; Audebert, P. (Chem. Rev., 2010)

(untitled) - Garau, C.; Quiñonero, D.; Frontera, A.; Costa, A.; Ballester, P.; Deyà, P. M. (Chem. Phys. Lett., 2003)